Genetic characteristics and phylogenetic analysis of three Chinese ethnic groups using the Huaxia Platinum System - Wang, Mengge (Sci Rep, 2018)
Short tandem repeats (STRs) are attractive to genetic applications like forensic, anthropological and population genetics studies. The Huaxia Platinum System was specifically developed to allow co-amplification and detection of all markers in the expanded CODIS core loci and the Chinese National Database. In this study, in continuation to our previous validation study, 568 unrelated individuals were firstly genotyped to investigate the effectiveness of this novel assay in 3 main ethnic groups of China (Han, Tibetan and Yi). The combined power of discrimination (CPD) were 0.9999999999999999999999999992, 0.999999999999999999999999992, 0.999999999999999999999999998, respectively, and the combined power of exclusion (CPE) were 0.9999999999, 0.999999995, 0.999999998, respectively. Next, genetic relationships along administrative and ethnic divisions were analyzed using pairwise genetic distances, multidimensional scaling (MDS), principal component analysis (PCA) and phylogenetic analysis. The Han ethnicity showed a high genetic homogeneity all across China, and significant genetic differences existed between Han groups and some minority groups, most prominently for the Tibetans, the Uyghurs, the Kazakhs, the Miaos, the Zhuangs and the Dais. Aforementioned results suggested that the Huaxia Platinum System is polymorphic and informative, which provides an efficient tool not only for human forensics, but also for population genetics studies.